Meningkatkan Keterampilan Sains Pada Anak Usia Dini Melalui Flipbook Berbasis Augmented Reality: Tinjauan Literatur Sistematis - Asyifa Maharani; Yaswinda; Nurhafizah; Setiyo Utoyo (Postgraduate, University of Mataram, 2026)
The integration of digital technology in education has encouraged the development of innovative learning media, including Augmented Reality (AR)-based flipbooks in science learning. Unlike previous studies that primarily focused on student motivation and conceptual understanding, this research emphasizes the novelty of integrating AR flipbook technology specifically to develop students’ science process skills in science learning. The study aimed to examine the effectiveness of AR-based flipbooks in improving students’ science process skills and learning engagement in junior high school science classes, particularly on the topic of the human digestive system. This study employed a quasi-experimental design with a pretest-posttest control group approach. The participants consisted of 64 eighth-grade students from a junior high school, divided into an experimental group (32 students) using AR-based flipbooks and a control group (32 students) using conventional learning media. The intervention was conducted over four weeks during science learning activities. Data were collected using science process skills tests, observation sheets, and student response questionnaires. The effectiveness of the media was analyzed using descriptive statistics, paired sample t-tests, independent sample t-tests, and effect size analysis. The results showed that the experimental group achieved a higher increase in science process skills compared to the control group. The average pretest score of the experimental group increased from 61.25 to 85.40 in the posttest, while the control group improved from 60.80 to 72.15. The N-gain score of the experimental group was 0.71 (high category), whereas the control group obtained 0.42 (moderate category). Statistical analysis revealed a significant difference between both groups (p < 0.05) with a large effect size (Cohen’s d = 0.87). Students in the experimental group also demonstrated better performance in observing, classifying, interpreting data, and communicating scientific findings. In addition, questionnaire results indicated that students showed higher motivation, active participation, and positive responses toward the use of AR-based flipbooks. In conclusion, AR-based flipbooks are effective and engaging learning media that significantly improve students’ science process skills and support active learning in science education. The integration of interactive AR features into science learning provides more meaningful and contextual learning experiences, making this media highly recommended for classroom implementation.